Pembentukan Personal Branding Melalui Media Sosial - Yohanna Eka Putri br Girsang; Ummanah Ummanah (Journal of Management and Bussines (JOMB), 2023)
This study aims to analyze the efforts, processes, and patterns of interaction carried out in the formation of personal branding by two content creators and travel bloggers, namely Canisisus Andrew and Veronika Desi through social media. The research method used is a case study with a single case research type and a unit of analysis with multiple case analysis. The theory that is used as a reference in analyzing efforts, processes, and patterns of interaction carried out in the formation of personal branding is Rampersad's theory, which is known as Authentic personal branding and EWOM. The results showed that the two research subjects succeeded in applying the ten criteria and the Authentic personal branding concept by Rampersad and applying the EWOM concept in their interactions by utilizing every feature and relationship they have on social media to continue to interact positively in building a positive image on each account. Instagram owned. Keywords: Content, Social Media, Personal Branding, Travel Blogger